2008
DOI: 10.1542/peds.2007-2711
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II Trial of High-Dose Erythropoietin in Extremely Low Birth Weight Infants: Pharmacokinetics and Safety

Abstract: Early high-dose recombinant erythropoietin is well tolerated by extremely low birth weight infants, causing no excess morbidity or mortality. Recombinant erythropoietin dosages of 1000 and 2500 U/kg achieved neuroprotective serum levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
148
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 41 publications
10
148
1
3
Order By: Relevance
“…This high‐dose rhEPO in rodents was equivalent to that in preterm infants given at a high dose of 1,000 to 2,500U/kg 20. Based on those results from neonatal rodent brain injury models, clinical studies showed that high‐dose rhEPO (2,500–3,000U/kg) administered after birth was well tolerated in preterm and term infants14, 20, 33, 37, 42 and conferred neuroprotection 16, 36. In a previous study using low‐dose rhEPO to prevent anemia in preterm infants, it was observed that preterm infants with rhEPO treatment also had significant neurodevelopmental improvement 38.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This high‐dose rhEPO in rodents was equivalent to that in preterm infants given at a high dose of 1,000 to 2,500U/kg 20. Based on those results from neonatal rodent brain injury models, clinical studies showed that high‐dose rhEPO (2,500–3,000U/kg) administered after birth was well tolerated in preterm and term infants14, 20, 33, 37, 42 and conferred neuroprotection 16, 36. In a previous study using low‐dose rhEPO to prevent anemia in preterm infants, it was observed that preterm infants with rhEPO treatment also had significant neurodevelopmental improvement 38.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments showed that high‐dose rhEPO (10,000–30,000U/kg) decreases both short‐term and long‐term brain injury, but it must be given at the time of, or very soon after, brain injury 12, 45. This high‐dose rhEPO in rodents was equivalent to that in preterm infants given at a high dose of 1,000 to 2,500U/kg 20. Based on those results from neonatal rodent brain injury models, clinical studies showed that high‐dose rhEPO (2,500–3,000U/kg) administered after birth was well tolerated in preterm and term infants14, 20, 33, 37, 42 and conferred neuroprotection 16, 36.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations